Effect of hot water treatment with calcium dips on postharvest quality of tomato - Wong, Jing Hao; Iffah Hazirah Mohd Nawi; Nor Idzwana Mohd Idris (Penerbit Universiti Kebangsaan Malaysia, 2020)
Tomato is fruit vegetables sustaining valuable benefits in economy and nutrition. It has a high content of Vitamin C and lycopene. Being a climacteric fruit, tomato is perishable and has a short shelf life. To improve the storage quality of tomato, the effect of hot water treatment and calcium dips on tomato (Solanum lycopersicum) was studied. Tomato fruits were dipped in two temperatures (40°C and 50°C) of the hot water bath for 2 minutes before treatment of 2% calcium chloride for 2 minutes. The fruits were stored at 10°C ± 2°C in the cold room at a relative humidity of 80-95%. Changes in weight loss, firmness, total soluble solids (TSS), titratable acidity, ascorbic acid, and lycopene content were observed and recorded on 0, 2, 4, 6, 8, 10, 12, 14 days of storage. Hot water treatment at 50°C with 2% of calcium chloride can control the weight loss and firmness of tomato with the low level of total soluble solids and acidity and retained the level of ascorbic acid. This treatment prone to extend shelf life, delay ripening and retained the postharvest quality of tomato.